Killing rage: ending racism - hooks, bell (Penguing Books, 1995)
"One of our country's premier cultural and social critics, bell hooks has always maintained that eradicating racism and eradicating sexism must go hand in hand. But whereas many women have been recognized for their writing on gender politics, the female voice has been all but locked out of the public discourse on race. Killing Rage speaks to this imbalance. These twenty-three essays are written from a black and feminist perspective, and they tackle the bitter difficulties of racism by envisioning a world without it"--Back cover.
Keywords: afro-féminisme; amériques; approches et analyses; féminismes noirs; justice sociale; racisme; régions géographiques; sexisme; systèmes d'oppressions; états-unis